Linguistic Signs in Slang Used in Drug Trading Transactions in Padang City - Amelia Yuli Astuti; Bram Denafri (Lingua Cultura, 2020)
The research discussed the linguistic sign in slang language used in drug transactions. Slang language was found based on interviews conducted with drug dealers and drug users in Ranah Parak Rumbio, South Padang subdistrict, Padang City. The aim of the research was to determine the signifier and signified found in drug slang language. Furthermore, the research determined the order of signification by analyzing the meaning of slang language based on its context. The data were obtained using the direct observation method. This was achieved by using interview techniques. The interviews were conducted with three informants. There were two men who used to be drug dealers and former drug users, and a woman who was an observer and anti-drug activist. Furthermore, the data were analyzed by using equalizing and differentiation techniques. Data analysis was carried out using semiotic by referring to the linguistic signs theory proposed by Saussure and the theory of order of signification by Barthes. In conclusion, it is found that slang is formed in word categories, abbreviations, and phrases. Then, the factors of language are also considered, such as time and place of the background, the number of participants in the interaction, talking topic, and interaction function. These factors then determine the use of slang terms between drug users and dealers.